Amoxycillin: pharmacokinetic studies in normal subjects, patients with pernicious anaemia and those with renal failure - Lawson, D. H. (1974)
This paper presents data on the absorption and disappearance of a new semisynthetic antibiotic—amoxycillin—in patients with pernicious anaemia and those with renal failure. Absorption of this drug is unimpaired in these patients. Adequate serum and urine levels are obtained even in patients with creatinine clearance levels below 10 ml/min. The half-life of this drug is markedly prolonged in patients undergoing regular dialysis therapy, and a single 250 mg dose will provide adequate serum levels for 24 hr, if this is given after dialysis is complete.